Metacognitive Awareness of Reading Strategies in Freshmen University Students - El Mekawy, Asmaa Ahmed (2014)
Metacognitive awareness presents a prerequisite for metacognition development among individuals. Researchers confirm that instruction of metacognition should be domain specific to motivate learners to adopt the practices that enhance their cognition and metacognition. Hence, the measurement of metacognition should be also domain specific. This has encouraged us to use Metacognitive Awareness of Reading Strategies Inventory (MARSI). The richness of the academic context in a country as U.A.E. is in desperate need for more investigations in the field of metacognition of its local and international students, and teachers. In this study, we examined the level of metacognitive awareness of reading strategies of freshmen university students (N = 169), followed by an examination of the reported strategy use of a subsample (n=29) compared to their actual strategy use when reading for studying. The results were quantitatively analyzed. One of the main findings in this study is that the students have medium to high levels of awareness, yet lack consistency between their self-reported and actual strategies. These findings and more are discussed in details demonstrating the theoretical and empirical implications.